2022
DOI: 10.1101/2022.02.25.481936
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Distinct subpopulations of DN1 thymocytes exhibit preferential γδ T lineage potential

Abstract: T cells are divided into the αβ and γδ lineages. It is currently thought that these lineages differentiate in the thymus from uncommitted progenitor thymocytes. However, in this study we show that the decision to differentiate into one or either lineage is in fact already fixed in these apparent uncommitted progenitors. Using single-cell RNA sequencing, we reassemble de novo a model of early T cell development based on the transcriptional profiles of individual CD4-CD8- double negative and γδ thymocytes. We sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 69 publications
3
6
0
Order By: Relevance
“…CD117 high versus CD117 low delineated DN2a versus DN2b cells as defined by the Rothenberg laboratory 5 and we recently showed that simultaneous inclusion of CD90 achieves better resolution. 3 Consistent with the scRNA-seq analysis (Figure 2), all DN1 subpopulations exhibited minimal cell cycling, with only about 5% of cells in S or G2/M phases (Figure 3). Also consistent with the scRNA-seq analysis, there was then a clear upregulation in cycling cells at DN2a, with one-quarter of cells in S or G2/M phases.…”
Section: Facs Analysis Confirms That Proliferation Is Upregulated At ...supporting
confidence: 79%
See 4 more Smart Citations
“…CD117 high versus CD117 low delineated DN2a versus DN2b cells as defined by the Rothenberg laboratory 5 and we recently showed that simultaneous inclusion of CD90 achieves better resolution. 3 Consistent with the scRNA-seq analysis (Figure 2), all DN1 subpopulations exhibited minimal cell cycling, with only about 5% of cells in S or G2/M phases (Figure 3). Also consistent with the scRNA-seq analysis, there was then a clear upregulation in cycling cells at DN2a, with one-quarter of cells in S or G2/M phases.…”
Section: Facs Analysis Confirms That Proliferation Is Upregulated At ...supporting
confidence: 79%
“…We recently published three 109 scRNA-seq data sets of DN thymocytes. 3 The first consisted of total DN and TCRcd + thymocytes, the second data set consisted only of DN1 and DN2 thymocytes and the third data set was generated from DN1/DN2, DN3 and TCRcd + thymocytes sorted separately and then mixed back together after sorting (Figure 1 and Supplementary figure 2). These sort strategies were employed to ensure that enough DN1 and DN2 thymocytes could be captured.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations